CARD SORT UNTUK MENGEMBANGKAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN IPAS - Atep Lesmana; Hany Handayani; Asep Nurhuda; Annisa Nurfitriani; Ihsan Rizali; Gemi Gustiani; Nurfatima Rachmasari; Mubarok Somantri (STKIP Subang, 2023)
This study aims to determine the effect of the Card Sort learning method on students' conceptual understanding abilities in science learning. The background of this research is that students often find it difficult to understand material, especially in science learning. PISA 2018 Results (Volumes I and II) stated that based on the results of the previous PISA survey, in 2018, Indonesia still ranked lower in the ability to understand concepts of elementary school students in all countries participating in the survey, therefore, fun learning is needed. so that students can focus and enthusiasm in learning. The research method used in this study was quasi-experimental or quasi-experimental with a Nonquivalent (Pretest and Posttest) Control Group Design. The population in this study were Grade IV students at SDN 1 Jatiluhur and the research samples taken were class IV A as an experimental class that applied the Card Sort learning method and class IV B as a control class that applied conventional learning. Data collection techniques using tests, observation, and documentation. The results of the analysis of research data on hypothesis testing obtained a significance result (2-tailed) of 0.001. Then a significance value of 0.001 <0.05 is obtained, meaning that there is an influence of the Card Sort learning method on students' conceptual understanding abilities in elementary school science learning. As well as the effect size test of the Cohens' d formula of 0.356 <d ≤ 0.5 which indicates the medium category. Both of these classes fall into the low category but the experimental class has a greater value than the control class. The results of this study indicate that the use of the Card Sort learning method has a moderate effect on students' conceptual understanding skills in science learning.